Nonovershooting and nonundershooting exact output regulation - Schmid, R.; Ntogramatzidis, Lorenzo (ELSEVIER, 2014)
We consider the classic problem of exact output regulation for a linear time invariant plant. Under the assumption that either a state feedback or measurement feedback output regulator exists, we give design methods to obtain a regulator that avoids overshoot and undershoot in the transient response.